Tax Compliance Behavior of E-Commerce MSMEs in Surabaya: Evidence from the E-Peken Platform - Hendrawati, Erna; Krivins, Anatolijs; Jaya, I Made Laut Mertha (International Journal of Social Science and Business, 2025)
The rapid shift of MSMEs in Indonesia toward government-initiated digital platforms such as E-Peken raises critical challenges of tax compliance, as prior research has overlooked how factors like tax regulation understanding, taxpayer awareness, socialization, collection mechanisms, and sanctions influence compliance behavior in locally bounded e-commerce ecosystems. This study investigates the influence of tax regulation understanding, taxpayer awareness, tax socialization, tax collection mechanisms, and tax sanctions on the compliance behavior of Micro, Small, and Medium Enterprises (MSMEs) operating on the E-Peken e-commerce platform in Surabaya, Indonesia. Using the Slovin formula to determine the sample size, the author obtained 351 MSME respondents. This primary Data were collected through a structured questionnaire and analysed using multiple linear regression with SPSS 23. The results show that understanding of tax regulations and taxpayer awareness significantly influence tax compliance, while tax socialization, collection, and sanctions have no significant effect. The model explains 49% of the variance in compliance, emphasizing the primacy of knowledge and awareness over enforcement. These findings suggest the need for tailored educational strategies and simplification of procedures, while theoretically reinforcing the Theory of Planned Behavior by highlighting the stronger role of cognitive and voluntary factors in shaping compliance.